2019
DOI: 10.1177/1129729819852550
|View full text |Cite
|
Sign up to set email alerts
|

Initial 3-year results of first human use of an in-body tissue-engineered autologous “Biotube” vascular graft for hemodialysis

Abstract: This study presents the initial 3-year results of the first in-human study of internal shunt restoration using completely autologous vascular grafts, “Biotubes,” based on in-body tissue architecture. Biotubes (diameter, 6 mm; length, 7 cm) were prepared as autologous collagenous tubular tissues with approximately 0.5 mm wall thickness by embedding molds (two per patient), assembled with a silicone rod and a stainless steel pipe with many slits, into the patients’ abdominal subcutaneous tissue for 2 months. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Aiming to fabricate an ideal vascular graft, multiple tissueengineered vascular grafts (TEVGs) have been developed using in vitro and/or in vivo tissue engineering technology, some of which have been clinically applied. 3,5,6,15 In vivo tissue engineering uses the patient's body as a bioreactor. Several groups have reported the development of a vascular graft that exploits the encapsulation that occurs when foreign materials are implanted under the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to fabricate an ideal vascular graft, multiple tissueengineered vascular grafts (TEVGs) have been developed using in vitro and/or in vivo tissue engineering technology, some of which have been clinically applied. 3,5,6,15 In vivo tissue engineering uses the patient's body as a bioreactor. Several groups have reported the development of a vascular graft that exploits the encapsulation that occurs when foreign materials are implanted under the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The research team also confirmed the use of Biotubes in clinical practice. 67 Biotubes with diameters of 6 mm and total lengths of 7 cm were similarly produced by implantation for 2 months in the abdominal subcutaneous tissue of patients who were undergoing hemodialysis. Although the implanted Biotubes led to stenosis for patients 4 months after the first surgery, this study has clinical significance because the first human case study was performed using autologous vascular constructs prepared by a molding technique.…”
Section: Conventional Strategy For Developing Vascular Constructsmentioning
confidence: 99%
“…Since its conception, the first developed mold as Biotube Maker has been a straight columnar type (original mold in Figure 1a), which is assembled by covering the outside of a plastic core rod with a stainless steel pipe with a predetermined gap space [30,35]. The pipe contains many thin slits.…”
Section: Development Of Original Straight Moldmentioning
confidence: 99%
“…Biotubes obtained from the straight mold have already been clinically applied to three dialysis patients as a First-in-Man (FIM) study [35]. Blood vessels on the venous side of the arteriovenous shunt are prone to stenosis.…”
Section: First-in-man (Fim) Study Of Straight Moldmentioning
confidence: 99%